Microbial consortium and biotransformation for pollution decontamination - Dar, Gowhar Hamid; Bhat, Rouf Ahmad, 1981-; Qadri, Humaira; Hakeem, Khalid Rehman (Advances in pollution research., 2022)
Microbial Consortium and Biotransformation for Pollution Decontamination presents techniques for the decontamination of polluted environs through potential microbes, particularly examining the benefits of its broad applicability, sustainability and eco-friendly nature. Utilizing global case studies to describe practical applications of the technology, the book offers insights into the latest research on advanced microbiological tools and techniques for the remediation of severe pollutants from the environment. Environmental researchers and environmental managers focusing on pollution and decontamination will find both key contextual information and practical details that are essential in understanding the use of microbial technology for combatting pollutants. Recent advancements in the field of NGS (next-generation sequencing) have allowed more detailed genomic, bioinformatics and metagenomic analyses of potential environmentally important microbes that have led to significant breakthroughs into key bio-degradative pathways. With the increase in human activities around the globe, toxic pollutants from multiple sources have contaminated the earth on a large number scale.